1998
DOI: 10.1046/j.1440-1614.1998.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of estimates of the prevalence of heavy drinkers in local regions of Queensland

Abstract: The NHS data appears to underestimate the population of heavy drinkers, whereas the Ledermann model overestimates it. In this situation, it seems preferable to use the more conservative self-report survey estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Underestimation has been observed as a problem in studies where self-assessment of exposures was used to obtain data on activities that are not socially acceptable such as smoking or alcohol abuse [Wagenknechet et al, 1992;Crook et al, 1998]. Our results indicated that underestimation of exposure was also a problem for selfreported solvent exposures.…”
Section: Validity Of Self-assessmentmentioning
confidence: 59%
“…Underestimation has been observed as a problem in studies where self-assessment of exposures was used to obtain data on activities that are not socially acceptable such as smoking or alcohol abuse [Wagenknechet et al, 1992;Crook et al, 1998]. Our results indicated that underestimation of exposure was also a problem for selfreported solvent exposures.…”
Section: Validity Of Self-assessmentmentioning
confidence: 59%